ANALISIS GEODESIK TIMELIKE UNTUK ORBIT LINGKARAN PADA BIDANG EKUATOR DALAM GEOMETRI KERR - Apta Premala, Aldowan
This thesis is devoted to study timelike geodesic in Kerr geometry for the circular orbit on a equatorial plane. We compute numerically the geodesic trajectory of the circular orbit. We analyze the accuracy of numerical computation by comparing the numerical result with exact calculation in null geodesic problem which can be solved analytically. The main focus of this thesis is to discuss the condition of circular orbit for a mass particle. We find that this orbit has stable and unstable states.